Engineering Two-Dimensional Nodal Semimetals in Functionalized Biphenylene by Fluorine Adatoms - Mo, Seongjun; Seo, Jaeuk; Son, Seok Kyun; Kim, Sejoong; Rhim, Jun Won; Lee, Hoonkyung (Nano Letters, 2024)
We propose a band engineering scheme on the biphenylene network, a newly synthesized carbon allotrope. We illustrate that the electronic structure of the biphenylene network can be significantly altered by controlling conditions affecting the symmetry and destructive interference of wave functions through periodic fluorination. First, we investigate the mechanism for the appearance of a type-II Dirac fermion in a pristine biphenylene network. We show that the essential ingredients are mirror symmetries and stabilization of the compact localized eigenstates via destructive interference. While the former is used for the band-crossing point along high symmetry lines, the latter induces highly inclined Dirac dispersions. Subsequently, we demonstrate the transformation of the biphenylene network’s type-II Dirac semimetal phase into various Dirac phases such as type-I Dirac, gapped type-II Dirac, and nodal line semimetals through the deliberate disruption of mirror symmetry or modulation of destructive interference by varying the concentration of fluorine atoms.
Keywords: American Chemical Society; Band engineering; Biphenylene; Destructive interference; Dirac semimetal; Flat band; Functionalized; Mirror symmetry; Two-dimensional; Type II; biphenylene; Dirac semimetal; flat band; fluorination